Sonocatalytic Degradation of Antibiotics Tetracycline by Mn-Modified Diatomite - Yiping Guo; Xiao Mi; Guoting Li; Xi Chen (Journal of Chemistry)
Mn-modified diatomite was prepared by wet impregnation and subsequent calcinations processes. It was used as catalyst for sonocatalytic degradation of antibiotics tetracycline. Characterizations by scanning electron microscopy and X-ray diffraction pattern showed that the morphology and crystal structure of the modified diatomite were similar to these of raw diatomite. Despite containing very limited amount of Mn oxides, the Mn-modified diatomite showed much higher sonocatalytic activity than the raw diatomite. The increases in both MnSO4 concentration of the wet impregnation solution and the catalyst dosage could enhance the degradation of antibiotics tetracycline significantly. Kapp values for ultrasonication, catalyst adsorption, and both processes combined (0.10 mol/L MnSO4-modified diatomite) were 1.22 × 10−4, 0.00193, and 0.00453 min−1, respectively, while the corresponding values of R2 were 0.956, 0.986, and 0.953, respectively. These results demonstrated the significant synergetic effect by combining ultrasonication and catalyst adsorption processes. The presence of isopropanol, KBr, and NaN3 quenched a series of reactive oxygen species sharply, indicating the dominant role of reactive oxygen species in the sonocatalytic process. In contrast, the addition of Fe(II) enhanced the degradation due to the generation of more OH∙ radicals in the concurrent Fenton reaction. All the results indicated that Mn-modified diatomite had the great potential for water treatment by sonocatalytic oxidation.